«Зеленая» экономика и энергоэффективность - Галушкина, Т.П.; Березовская Ю.В.; Лёгкая, Е.В. (Економічні інновації, 2013)
Розглядаються еколого-економічні аспекти проблеми розвитку «зеленої» енергетики як ключового сектору економіки України. Запропоновано шляхи підвищення енергоефективності у контексті модернізації та розвитку національної енергетики. The environmental and economic aspects of the development of "green" energy as a key sector of the economy of Ukraine are considered in this article. The ways of improving energy efficiency in the context of modernization and development of the national energy sector are proposed.